Endoplasmic reticulum stress-induced apoptotic pathway and mitochondrial dysregulation in HeLa cells treated with dichloromethane extract of Dillenia suffruticosa - Wan Nor Hafiza, Wan Abd Ghani (Pharmacogn Mag, 2016)
Ethyl acetate and dichloromethane extract of Dillenia suffruticosa (EADS and DCMDS, respectively) can be a potential anticancer agent. The effects of EADS and DCMDS on the growth of HeLa cervical cancer cells and the expression of apoptotic-related proteins had been investigated in vitro. Cytotoxicity of the extracts toward the cells was determined by 5-diphenyltetrazolium bromide assay, the effects on cell cycle progression and the mode of cell death were analyzed by flow cytometry technique, while the effects on apoptotic-related genes and proteins were evaluated by quantitative real-time polymerase chain reaction, and Western blot and enzyme-linked immunosorbent assay, respectively. Treatment with DCMDS inhibited (P < 0.05) proliferation and induced apoptosis in HeLa cells. The expression of cyclin B1 was downregulated that led to G(2)/M arrest in the cells after treatment with DCMDA. In summary, DCMDS induced apoptosis in HeLa cells via endoplasmic reticulum stress-induced apoptotic pathway and dysregulation of mitochondria. The data suggest the potential application of DCMDS in the treatment of cervical cancer.